Research on Color Attention Bias Caused by Olfactory Stimulation in Visual Search Task - Bai, Hexin; Zhang, Haibin (Transactions on Materials, Biotechnology and Life Sciences, 2024)
People often connect and integrate information from different sensory channels to form cross-channel connection. Previous studies have proved that vision, as a dominant perception, will affect the perception and recognition of olfactory channels. This study attempts to prove experimentally that olfactory channels have an influence on the perception and recognition of visual information. Experimental method: Subjects were asked to search the target with a specific shape visually after deeply smelling fragrance card, and their respective reaction time was tested. The indicative of olfactory stimuli is regarded as an intragroup variable, and the forward and reverse correlation between target color and olfactory stimuli is regarded as an inter-group variable. The experimental results show that when the color associated with olfactory stimulation appears on the target pattern, it will speed up the visual search, but when the color associated with olfactory stimulation appears on the interference pattern, it will hinder the visual search speed. Conclusion: It is proved that olfactory cues will lead to visual attention bias to its associated colors, indicating that there is a cross-channel influence of olfactory stimuli on visual attention.